2020
DOI: 10.1093/mnras/staa3893
|View full text |Cite
|
Sign up to set email alerts
|

The time-scales probed by star formation rate indicators for realistic, bursty star formation histories from the FIRE simulations

Abstract: Understanding the rate at which stars form is central to studies of galaxy formation. Observationally, the star formation rates (SFRs) of galaxies are measured using the luminosity in different frequency bands, often under the assumption of a time-steady SFR in the recent past. We use star formation histories (SFHs) extracted from cosmological simulations of star-forming galaxies from the FIRE project to analyse the time-scales to which the H α and far-ultraviolet (FUV) continuum SFR indicators are sensitive. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 86 publications
(53 citation statements)
references
References 82 publications
4
49
0
Order By: Relevance
“…We see that the relative variance is much larger at early times than at late times, consistent with previous studies (e.g. Stern et al 2020;Flores Velázquez et al 2021) that have shown that star formation in massive FIRE-2 galaxies tends to transition from bursty to steady as we approach the present day.…”
Section: Bursty Phase Steady Phase and Age Distributionssupporting
confidence: 92%
“…We see that the relative variance is much larger at early times than at late times, consistent with previous studies (e.g. Stern et al 2020;Flores Velázquez et al 2021) that have shown that star formation in massive FIRE-2 galaxies tends to transition from bursty to steady as we approach the present day.…”
Section: Bursty Phase Steady Phase and Age Distributionssupporting
confidence: 92%
“…We see that the relative variance is much larger at early times than at late times, consistent with previous studies (e.g. Stern et al 2020;Flores Velázquez et al 2021) that have shown that star formation in massive FIRE-2 galaxies tends to transition from bursty to steady as we approach the present day.…”
Section: Bursty Phase Steady Phase and Age Distributionssupporting
confidence: 91%
“…We note that in the FIRE simulations, the resolved ISM produces star formation histories that are generically bursty for dwarf galaxies (e.g. Sparre et al 2017;Faucher-Giguère 2018;Flores Velázquez et al 2021), an effect which can be suppressed in lower-resolution simulations that use simplified ISM prescriptions. The mass of the individual star particles is sufficiently small to support the assumption that each represents a single-age, single-metallicity stellar population while still being large enough to fully sample the IMF at the high-mass end (Sanderson et al 2020).…”
Section: The Fire Simulationsmentioning
confidence: 94%